(untitled) (Journal of EAHIL, 2024)
In part I of this article, published in this same issue of the Journal of EAHIL, we set the background for the NHS in England context looking at the drivers, strategy, and actions taken to develop the Knowledge and Library Services (KLS) workforce. In this piece we provide a snapshot of how services are testing and beginning to adopt artificial intelligence (AI) in their practice. It also reflects on the role of KLS in educating the workforce and provides the challenge to adopt AI and skilfully weave into all we do until it becomes business as usual.